Analysis of Student Satisfaction Index on the Quality of Practical Guidance Services by Lecturers of the D-III Medical Laboratory Technology Study Program, East Kalimantan Ministry of Health Polytechnic - Hartini, Supri; Wartini, Sri; Warman, Warman; G, Widyatmike; Haryaka, Usfandi (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
Poltekkes Kemenkes East Kalimantan is the only state university in the health sector that has several departments. One of the departments at Poltekkes East Kalimantan is D-III Medical Laboratory Technology (TM). The vision of the TLM department is to become a study program that produces quality D-III TLM personnel, superior in the field of health microbiology, competitive at the national level and with a global perspective. Students' practical abilities are directly proportional to teacher services in classroom practical guidance. Vocational education at Poltekkes focuses on developing practical abilities through a skills-based approach and practices such as health centers, hospitals, laboratories, and clinics. The purpose of the practice is to obtain technical competencies that are relevant to industry needs, especially in the health sector. The purpose of this study was to measure the student satisfaction index towards the practical services of the D-III Medical Laboratory Technology Study Program. This research method is a quantitative approach using a descriptive method with a total sampling of 229 students. The results of the study showed a very satisfactory level of student satisfaction with all aspects with values of 88.21%, 94.32%, 91.27%, 89.52%, 91.79%, 90.74%, 89.69%, 89.52%, 90.22% and 93.54% with an average of 90.88% included in the dangerous category okay. The IKM value obtained was 81.5, which means it has a quality value of "A" or its performance is very good.